Evaluation of specialized training in hospital pharmacy - María José Gimeno-Jordá; Teresa Giménez-Poderos; Eva Negro-Vega; Edurne Fernández-de Gamarra; Patricia Sanmartín-Fenollera; Ana Lozano-Blázquez; Jaime González-López; Amparo Talens-Bolós; Raquel Arrieta-Navarro; Manuel Soria-Soto (Farmacia Hospitalaria, 2020)
Objective: To analyze the degree of satisfaction of hospital pharmacy residents and identify areas of improvement in their training. Method: A survey (5-point Likert scale) was administered among fourthyear hospital pharmacy residents due to complete their residency in 2018. Bivariate and multivariate logistic regression analyses was performed to identify the association of each independent variable with overall satisfaction. Results: 67.4% (91/135) of residents filled out the questionnaire. The mean overall satisfaction rate was acceptable-good (3.52 ± 0.92); 86.8% of residents had received an individualized training program, with 50% of them considering their individualized training program to be very well attuned to their day-to-day professional practice. The work of the tutor and other staff members involved in resident education was rated as positive by 63.7% and 72.5% of residents, respectively. A total of 15.4% of residents said that their units had a supervision and progressive empowerment protocol in place. With respect to the level of on-call responsibility bestowed on them, 81% of residents considered it to be adequate; 69.2% considered the supervision they received to be adequate. As many as 96.7% of residents dedicated less than 10 hours per week to teaching or research activities; 35.2% of residents had produced five or less articles or congress presentations as first authors. Residents that had defended or were in the process of writing their PhD dissertation were 30.8%; 45.1% were involved in an Research project. Finally, 89% of residents rated the training received as positive, with 75.8% of them stating that they would select the same hospital again. In the statistical analysis, an association was found between overall satisfaction and several variables, with the work done by the main tutor being independently related to overall satisfaction. Conclusions: Overall satisfaction with the training received by fourthyear residents was acceptable. The work of the tutor and other staff members involved in resident education were the variables with the greatest influence on overall satisfaction, albeit only the tutor´s work achieved statistical significance. The supervision of residents’ progress, the coaching provided by other staff members during clinical rotations, and research were identified as areas for improvement.